Pengaruh Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan Perusahaan (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020 – 2022) - Butar, Winda Anastasya Butar; Gaol, Manatap Berliana Lumban; Manurung, Amran (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of Corporate Social Responsibility (CSR) on financial performance in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2022. The population used was 84 companies. By using Purposive Sampling techniques, the sample obtained was 51 companies. The independent variable used is Corporate Social Responsibility (CSR) while the dependent variable is financial performance which is proxied by Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS). This study uses quantitative research. The data used is secondary data collected using the documentation method. The analytical method used is simple linear regression analysis using SPSS Version 25 software. The study results show that Corporate Social Responsibility (CSR) has a positive and significant effect on Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS).